UML Diagram E-Learning Application: A Pilot Study - Ramle, Rosni; Kamalruddin, Muhammad Aqil Fahmiruddin; Ismail, Muhammad Isa; Zaina, Muhammad Zakwan (Multidisciplinary Applied Research and Innovation, 2020)
Unified Modelling Language diagrams is a topic in Universiti Tun Hussein Onn Malaysia’s Diploma in Information Technology’s Object-Oriented Programming course, used to graphically present system entities and or flow, for better understanding of a system during its design. Students were found to have trouble differentiating the purpose of and how to draw the diagrams. This paper proposed a learning application for self-regulated learning of the topic. The application designed using the ADDIE model, developed using Adobe Flash and tested by 10 Diploma in Information Technology students in Universiti Tun Hussein Onn Malaysia. Results of usability survey are generally positive, with rooms for improvement in terms of design and navigation.